Pregnancy with chronic kidney disease: maternal and fetal outcome. (September 2016) - Bharti, Juhi; Vatsa, Richa; Singhal, Seema; Roy, Kallol Kumar; Kumar, Sunesh; Perumal, Vanamail; Meena, Jyoti
Abstract: Objective: Pregnancy with chronic kidney disease (CKD) is considered to be high risk. The purpose of this study was to assess the effect of pregnancy on CKD and the fetomaternal outcome in these patients. Study design: A retrospective observational study was conducted in the Department of Obstetrics and Gynaecology, All India Institute of medical sciences, New Delhi over a period of 11 years. A total number of 80 pregnant patients with CKD were reviewed. Staging of CKD was done according to glomerular filtration rate (GFR). Maternal demographic profile, stage of CKD, biochemical profile, antenatal and neonatal records were analyzed. The course of pregnancy was then reviewed and note was made of any maternal or fetal complication. At the time of analysis, patients were divided into early (Stage 1, 2) and late stage (Stage 3–5) disease. All the variables were compared between two groups. Data analysis was carried out using SPSS software version 20.0. Results: There was significantly increased incidence of preeclampsia ( p = 0.001) and moderate to severe anemia ( p = 0.001) in late stage disease as compared to early stage. The renal parameters including mean GFR and serum creatinine deteriorated with pregnancy in both the groups. Among fetal complications, the patients in late stage had significantly increased incidence of small for gestational age, low 5 min Apgar score and increased NICU admissions. The overall preterm delivery rate was 57.5%. There was an overall increase in the incidence of caesarean section (CS) rate (64%). Conclusions: Despite advances in antenatal care, incidence of adverse events in mother and fetus remain high in these women of CKD as compared to the rates expected in the general population. In all patients of CKD planning for pregnancy, the pre-existing disease should be optimized before conception.